How the U.S. Government's Market Activities Can Bolster Mobile Banking Abroad - Colin C. Richard (Washington University Law Review, 2011)
To combat corruption and increase the effectiveness of foreign aid, the United States should require that all of its foreign aid distributions, reconstruction projects, and payments for services abroad go through banking channels — that is, the U.S. government should strive to eliminate cash transactions whenever possible. In U.S. operations in many parts of the developing world, this will mean utilizing nascent mobile banking industries, an event that will have numerous positive results for these economies.
Keywords: Electronic funds transfers; Electronic banking; International economic assistance; Government policy